Agenda Empowerment of People in Tarmizi Taher Point of View - Mawardi Mawardi; Hasyimsyah Hasyimsyah; Amroeni Drajat (Budapest International Research and Critics University, 2019)
This study aims to explore agenda empowerment of people in Tarmizi Taher point of view. Tarmizi Taher in his book harmony of religious life and study of religions, that religious harmony can be formed by supporting harmonious religious communities, it is necessary for clerics, da’i (preachers), priests, priests and other religious leaders to instill to people about the inevitability of religious pluralism in social life. That the diversity of religions is a fact that cannot be denied. So the consequence is that every religious community has an obligation to recognize and respect other religions, without the need to elevate or demean a religion. The result shows that in Tarmizi Taher's view, community empowerment can be done by providing skills education conducted by the government so that people can compete with the advancement of science and technology.